Specific degradation of phosphatidylglycerol is necessary for proper mitochondrial morphology and function - Pokorná, Lucia; Čermáková, Petra; Horváth, Anton; Baile, Matthew G; Claypool, Steven M; Griač, Peter; Malínský, Jan; Balážová, Mária (Biochimica et biophysica acta, 2016)
In yeast, phosphatidylglycerol (PG) is a minor phospholipid under standard conditions; it can be utilized for cardiolipin (CL) biosynthesis by CL synthase, Crd1p, or alternatively degraded by the phospholipase Pgc1p. The Saccharomyces cerevisiae deletion mutants crd1Δ and pgc1Δ both accumulate PG. Based on analyses of the phospholipid content of pgc1Δ and crd1Δ yeast, we revealed that in yeast mitochondria, two separate pools of PG are present, which differ in their fatty acid composition and accessibility for Pgc1p-catalyzed degradation. In contrast to CL-deficient crd1Δ yeast, the pgc1Δ mutant contains normal levels of CL. This makes the pgc1Δ strain a suitable model to study the effect of accumulation of PG per se. Using fluorescence microscopy, we show that accumulation of PG with normal levels of CL resulted in increased fragmentation of mitochondria, while in the absence of CL, accumulation of PG led to the formation of large mitochondrial sheets. We also show that pgc1Δ mitochondria exhibited increased respiration rates due to increased activity of cytochrome c oxidase. Taken together, our results indicate that not only a lack of anionic phospholipids, but also excess PG, or unbalanced ratios of anionic phospholipids in mitochondrial membranes, have harmful consequences on mitochondrial morphology and function.
Keywords: Mitochondria; Saccharomyces cerevisiae; fosfolipasy; Respiration; mitochondrie; respirační komplex IV; fosfatidylglyceroly; Cardiolipins; Electron Transport Complex IV; Phosphatidylglycerol; Yeast; Phosphatidylglycerols; Phospholipases; Morphology; kardiolipiny